Influence of Milling and Aging on Cooking properties of Indigenous Aromatic Rice - Rayaguru, Kalpana; Pandey, J P (Journal of Agricultural Engineering, 2009)
Freshly harvested rice grains exhibit poor milling and cooking characteristics and the desirable properties are acquired during the short maturation period (aging). Experiments were conducted with indigenous variety of aromatic rice, Chinikamini, to study the effects of degree of milling (under milled, well milled and over milled) and aging (0 to 180 days) on quality aspects of aromatic paddy and milled rice. With the progress of aging, milling yield remained 72.19% ((±0.5%), while the head rice recovery increased from 66.29% (freshly harvested) up to 68.4 % after 180 days of aging. The kernel elongation ratio and volume expansion ratio increased while solid loss, alkali digestion score and gel consistency values decreased. The amylose content remained constant with aging. but the hot water insoluble fraction of amylose increased. The rate of improvement in the cooking properties was faster during the initial 3 to 4 months of aging, thereafter the rate decreased. The effect of degree of milling on quality changes during aging was significant, and reflected more in well milled rice than that in under milled rice. The degree of milling more than 10% (over milled) did not influence these results much. Paddy samples behaved distinctly intermediate between under milled and well milled samples. The study concluded that hot water insoluble amylose content may be a major determinant of cooked rice properties as it showed higher correlation coefficient (&gt0.95). However, kernel elongation ratio may be the next appropriate parameter to be used as an aging index.